2004
DOI: 10.1143/jjap.43.1602
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown Characteristics of Porous Metals

Abstract: We give first an approximation of the operator δ h :, is a Hamilton function and * h denotes the star product. The operator, which is the generator of time translations in a * h-algebra, can be considered as a canonical extension of the Liouville operator L h : f → L h f := {h, f } Poisson . Using this operator we investigate the dynamics and trajectories of some examples with a scheme that extends the Hamilton-Jacobi method for classical dynamics to Moyal dynamics. The examples we have chosen are Hamiltonians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3][4][5] As for multichannel gap switches, the shorter the formative and statistical time lags of each gap, the larger the number of arc channels. As we examined the breakdown characteristics of a sphere/plane gap using a mirror-finished brass plate and a porous metal as plane electrodes, we confirmed that the formative and statistical time lags decrease when porous metals are used as a discharge electrode, 6) so the number of arc channels of a self-breakdown-type railgap with a porous metal is expected to increase. We compared the results of the railgap using a mirror-finished brass plate and a porous metal as one of the electrodes of the railgap.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…[1][2][3][4][5] As for multichannel gap switches, the shorter the formative and statistical time lags of each gap, the larger the number of arc channels. As we examined the breakdown characteristics of a sphere/plane gap using a mirror-finished brass plate and a porous metal as plane electrodes, we confirmed that the formative and statistical time lags decrease when porous metals are used as a discharge electrode, 6) so the number of arc channels of a self-breakdown-type railgap with a porous metal is expected to increase. We compared the results of the railgap using a mirror-finished brass plate and a porous metal as one of the electrodes of the railgap.…”
Section: Introductionmentioning
confidence: 55%
“…The formative and statistical time lags of a single gap of 1 mm are smaller than those of 3 mm and 5 mm, shown in ref. 6. Also, the formative and statistical time lags of single gap with the porous metal are smaller than those with the mirror-finished plate, so it is easy to produce the multichannel operation in the case of the gap length of 1 mm with the porous metal.…”
Section: Number Of Arc Channels When Parameters Are Changedmentioning
confidence: 99%
“…We have demonstrated that CF 4 production in PFC plasmas advances significantly not only in the etching region of SiO 2 but also in the downstream region of the plasmas. 4) This finding suggests that inserting a device between the wafer and the suction port of a vacuum pump could prevent the production of CF 4 in the process chamber. The study of the reaction mechanism in the PFC plasmas would also lead to realizing in situ abatement of the high-GWP PFCs in PFC plasma processes.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It is necessary to research the low-permittivity and low-loss ceramics used at higher frequency to meet the growing work frequency of microwave components. Several kinds of common low dielectric constant of microwave dielectric ceramics such as (Zn,Mg) 2 [5][6][7][8][9][10][11][12][13][14] The microwave dielectric properties of ZnAl 2 O 4 ceramics have been reported in recent years. Surendran et al 15 found ZnAl 2 O 4 ceramics had good microwave dielectric properties of e r = 8.5, Q 9 f = 57,000 GHz and s f = À79 ppm/°C in 2004.…”
Section: Introductionmentioning
confidence: 99%